KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA POSITIF TERINTEGRASI BUDAYA INDUSTRI - Ariani, Dian; Yoto, Yoto (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2025)
ABSTRACT The leadership of a school principal plays a central role in shaping the direction, quality, and overall atmosphere of the school culture, particularly in building a positive environment that is integrated with the demands of the industrial world. This article focuses on the leadership of the principal of SMKN 1 Boyolangu in constructing a positive school culture aligned with industrial culture as a strategic response to the challenges of globalization and workplace competition. The study is motivated by the observed gap between existing school culture and the work ethics required by industry, which calls for leadership capable of bridging both spheres. This research applies a descriptive qualitative approach using data collection techniques such as observation, in-depth interviews, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal that the principal plays a strategic role in fostering values of discipline, responsibility, integrity, and collaboration as core elements of school culture. Furthermore, systematic efforts have been made to harmonize school programs with industrial standards, such as competency-based curriculum development, strengthening partnerships with business and industry (DUDI), and creating a learning environment that emphasizes professional work ethics. The main conclusion highlights that visionary, participatory, and adaptive leadership successfully builds a positive school culture that not only supports students’ character development but is also relevant to industrial culture, thereby equipping graduates with better readiness to face the challenges of the workforce. ABSTRAK Kepemimpinan kepala sekolah memiliki peran sentral dalam menentukan arah, kualitas, sekaligus atmosfer budaya yang berkembang di lingkungan sekolah, khususnya dalam membangun budaya positif yang terintegrasi dengan kebutuhan dunia industri. Artikel ini berfokus pada kepemimpinan kepala sekolah SMKN 1 Boyolangu dalam mengkonstruksi budaya positif yang selaras dengan budaya industri, sebagai upaya menjawab tantangan era globalisasi dan persaingan kerja. Penelitian dilatarbelakangi oleh fenomena masih ditemukannya ketimpangan antara budaya sekolah dengan tuntutan budaya kerja industri, sehingga dibutuhkan strategi kepemimpinan yang mampu menjembatani keduanya. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Analisis dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepala sekolah memainkan peran strategis dalam menanamkan nilai disiplin, tanggung jawab, integritas, dan kolaborasi sebagai bagian dari budaya sekolah. Selain itu, terdapat upaya sistematis dalam menyinergikan program sekolah dengan standar industri, seperti penyusunan kurikulum berbasis kompetensi, peningkatan kerjasama dengan dunia usaha dan dunia industri (DUDI), serta penciptaan lingkungan belajar yang menekankan etos kerja profesional. Simpulan utama penelitian ini adalah kepemimpinan kepala sekolah yang visioner, partisipatif, dan adaptif mampu membangun budaya positif yang tidak hanya mendukung perkembangan karakter peserta didik, tetapi juga relevan dengan budaya industri, sehingga lulusan memiliki kesiapan yang lebih baik dalam menghadapi tantangan dunia kerja.